Profile of Children with Undernutrition Admitted in Two Secondary-Level Hospitals in Maputo City, Mozambique - Cossa-Moiane, Idalécia (2024)
This research was undertaken as part of a Ph.D. program. This was funded by the FlemishInternational Cooperation Agency (FICA) under the Building Institutional Capacity Mozambican INS (BICMINS) project within ITM and INS (DiV-PA-20140910).